2021
DOI: 10.3390/molecules27010180
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Silver and Electrical Treatment for Susceptibility and Disinfection of Escherichia coli Biofilm-Contaminated Titanium Surface

Abstract: In this work, surface disinfection and biofilm susceptibility were investigated by applying ionic silver of 0.4–1.6 µg/mL and cathodic voltage-controlled electrical treatment of 1.8 V and a current of 30 mA to Escherichia coli (E. coli) ATCC 25922 biofilm-contaminated titanium substrates. Herein, it is evident that the treatment exhibited the potential use to enhance the susceptibility of bacterial biofilms for surface disinfection. In vitro studies have demonstrated that the ionic silver treatment of 60 min s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Besides acting as a pre-agglomeration stabilizer to obtain high dispersion of the primary cellulose filler in NRL, SCMC is also a stabilizer of silver nanoparticles (AgNPs) [ 17 ], which is adopted to enhance antimicrobial property to NR composites in this study. AgNP-based biopolymers offer good biocompatibility and biodegradability and can be considered as an effective material for application in antimicrobial packaging and pharmaceutical and medical fields [ 18 , 19 , 20 , 21 ]. The antimicrobial effect of Ag has been previously demonstrated against many types of microorganisms, including bacteria, viruses, and protozoa [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides acting as a pre-agglomeration stabilizer to obtain high dispersion of the primary cellulose filler in NRL, SCMC is also a stabilizer of silver nanoparticles (AgNPs) [ 17 ], which is adopted to enhance antimicrobial property to NR composites in this study. AgNP-based biopolymers offer good biocompatibility and biodegradability and can be considered as an effective material for application in antimicrobial packaging and pharmaceutical and medical fields [ 18 , 19 , 20 , 21 ]. The antimicrobial effect of Ag has been previously demonstrated against many types of microorganisms, including bacteria, viruses, and protozoa [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…AgNP-based biopolymers offer good biocompatibility and biodegradability and can be considered as an effective material for application in antimicrobial packaging and pharmaceutical and medical fields [ 18 , 19 , 20 , 21 ]. The antimicrobial effect of Ag has been previously demonstrated against many types of microorganisms, including bacteria, viruses, and protozoa [ 18 , 19 , 20 , 21 ]. It has been shown that AgNPs exhibit strong antibacterial activities against both Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Suttasattakrit and coauthors [19] determined that the applications of electric currents creates a synergistic effect on the antibacterial effect of silver. The researchers obtained an effective antibacterial and antibiofilm result compared to the model without ionic silver and current.…”
Section: Introductionmentioning
confidence: 99%